Perbandingan Kualitas Butir Tes Buatan Guru pada Penilaian Sumatif Semester Ganjil Mata Pelajaran Bahasa Indonesia Kelas XI di SMKN 2 Palangka Raya dan Kelas XI di SMKN 3 Palangka Raya Tahun Ajaran 2023/2024 - Melina Pebrianti; Petrus Poerwadi; Lazarus Linarto; Paul Diman; Ibnu Yustiya Ramadhan (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
This research aims to determine the quality of teacher-made test items in the summative assessment of Indonesian language subjects in class XI at SMKN 2 Palangka Raya and class XI at SMKN 3 Palangka Raya in the 2023/2024 academic year. This research is quantitative descriptive. Data was obtained using the documentation method, namely answer keys, student answers, student scores and test items. The population of this study was all class XI students at SMKN 2 Palangka Raya and all class XI students at SMKN 3 Palangka Raya. The samples for this research were students of class XI MPLB 3 (Office Management and Business Institutions 3) at SMKN 2 Palangka Raya and students of class The data obtained was analyzed using the Microsoft Excel program and the SPSS version 25 for Windows program. The results of this research show that, 1) Level of Difficulty, the test items from the two schools have differences in terms of percentage between easy, medium and difficult question categories. 2) Differential power, the test items from the two schools show differences in terms of percentage between categories with good, sufficient and low differentiating power. 3) Distraction, the test items from the two schools have differences in terms of percentage between question categories with very good, good and not good levels of distraction.